Tropical Asian mega‐delta ponds: Important and threatened socio‐ecological systems. Issue 2 (21st October 2021) - Moorhouse, Heather L.; Roberts, Lucy R.; McGowan, Suzanne; Panizzo, Virginia N.; Barker, Philip; Salehin, Mashfiqus; Do, Thu Nga; Nguyen Thanh, Phong; Rahman, Mohammad Feisal; Ghosh, Tuhin; Das, Sourav; Hackney, Christopher; et al.
Abstract: This paper uses multimedia to showcase the narratives and lived experiences of those who live and work in tropical Asian mega‐deltas, and as such is the first journal article of its kind in the field of Regional Geography. Using videos, photography and audio this paper describes the characteristics of ponds and their place in the intrinsically connected human‐environmental fabric of these delta regions. The aim is to bring to life descriptive inventories and provide greater weight in support of our conclusion that tropical Asian mega‐delta ponds are important and threatened systems. River deltas comprise just 1% of land cover worldwide but support the livelihoods of more than 500 million people. Delta research has historically focused on the major river channels and the socio‐ecological role of ponds has been overlooked despite their large number and surface area. Ponds are intrinsically linked to daily life (potable water, sanitation, bathing, washing), industry (aquaculture, agriculture) and the natural‐cultural heritage (religion, folklore) of deltas. In contrast to the larger river channels, ponds are likely to be significant stores and processors of nutrients, including carbon, and pollutants at annual to decadal scales, on account of their heavy anthropogenic use and smaller individual sizes. Consequently, they are severely polluted water sources and pose significant public health risks. In this review, we use case studies from three Asian mega‐deltas (the Red River Delta and the Mekong River Delta, Vietnam, and the Ganges‐Brahmaputra‐Meghna Delta, India and Bangladesh) to highlight the importance of Asian mega‐delta ponds as important socio‐ecological systems in their own right. We discuss future environmental challenges, knowledge gaps on the ecological function and biodiversity of these habitats, management and policy practices, and the capacity of ponds to achieve the UN Sustainable Development Goals. Abstract : The role of Asian mega‐delta ponds as important socio‐ecological systems is investigated in this review. These systems have the capacity to deliver food and water provisional services but their intrinsic link to wider Asian mega‐delta socio‐ecological stressors and impacts, such as over‐population and intensification of human activity challenges the ability of these systems to deliver services such as water security and satisfy UN Sustainable Development Goals such as Goal 6. Clean Water and sanitation.